Linking Upanisads to Life - Sharma, Yam Prasad (Achyutram Bhandari Sangit Pratisthan Aalekh, 2026)
Upanisads present the ways of joyful life. Competition, fear, pain, suffering, failure, tragedy, decay and destruction make the life horrible and unbearable. Upanisads provide solace and peace of mind in such situation. When we understand the significances of the texts, we become full of kindness, empathy, compassion, cooperation and harmony, for we identify ourselves with all the beings and things of the universe. Some of the principal statements of Upanisads affirm the oneness of the individual self and the universe (Brahma). The statement Aham Brahmasmi means that I am Brahma (universe). Next statement Sarvaṃ Khalvidaṃ Brahma means that all this is Brahma. This is Brahma. That is Brahma. Both the subject and object are the one. This is the awareness and realization of oneness of all beings and all things in the universe. Furthermore, next expression in Upanisad is ‘Tattvamasi (Tat tvam asi) which means that ‘that you are’. The statement suggests that ‘you are that (thing) which you are in the quest of.’ The subject itself becomes the object. The searcher of the essence is itself the essence (tatva). These statements suggest the oneness of Brahma including all conscious beings and non-beings. We all are within the Brahma. I am within you. You are within me. You and I are one. When we realize this, there is no comparison, hierarchy and judgment. Since everything is indestructible infinite Brahma, there is no fear of loss, failure and death. The causes of pain and suffering disappear since all the things are the expressions of same entity (Brahma). This state is called Satchitanand (Sat-chit-anand). This means that realization of the truth (essence) provides absolute bliss. The life is full of perpetual joy. Such outlooks in Upanisads give immense strength to face all sorts of difficulties in life. The life becomes celebration.